Comparison of the effectiveness of different counseling methods before second trimester genetic amniocentesis in Thailand. (16th September 2013) - Hanprasertpong, Tharangrut; Rattanaprueksachart, Rawiwan; Janwadee, Suthiraporn; Geater, Alan; Kor‐anantakul, Ounjai; Suwanrath, Chitkasaem; Hanprasertpong, Jitti
ABSTRACT Objective The objective of this study is to compare the effectiveness of counseling methods before second trimester genetic amniocentesis. Study design The design of this study is a randomized controlled study comparing the improvement in patients' knowledge satisfaction anxiety and perceived pain between computer‐assisted instruction (CAI) and leaflet self‐reading (LSR) and subsequent individual counseling among pregnant women scheduled for second trimester genetic amniocentesis in a developing country. Results There were 164 and 157 participants in the LSR and CAI groups, respectively. In both groups, knowledge improved significantly after LSR/CAI (p < 0.001) and increased further after individual counseling (p < 0.001). After combined counseling, knowledge was significantly higher in the LSR than in the CAI group (p = 0.032). Knowledge was associated with higher level of education and previous exposure to genetic counseling. Pain decreased more in the CAI than in the LSR group after completion of counseling (p = 0.021). Reduction in anxiety and increase in satisfaction did not differ between the groups. Counseling method did not affect the final decision of patients to accept amniocentesis. Conclusion Both counseling methods improved patients' knowledge and satisfaction and reduced pain and anxiety. In combination with individual counseling, LSR was more effective than CAI in improving patients' knowledge before second trimester genetic amniocentesis. © 2013 John Wiley & Sons, Ltd.